Analisis Penerimaan Pajak Parkir dan Kontribusinya terhadap Pendapatan Daerah Kota Medan: Penelitian - Jessica Octavia Abigael Sibarani; Tengku Eka Susilawaty; Junawan (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study analyzes parking tax revenue and its contribution to Medan City's Regional Original Revenue (PAD) for 2020-2022. Using a descriptive quantitative approach, primary data was obtained from the Medan City Regional Revenue Agency (BPD) through documentation techniques. The sample was taken using a purposive sampling method. Data analysis used an effectiveness ratio and contribution formula. The results show that despite the increasing number of vehicles, the contribution of parking tax to PAD is very low and inconsistent. Illegal parking practices and inaccurate parking spot data result in lost revenue potential. The contribution of parking tax to Medan City's PAD ranges from 0.51% to 1.09%, with significant fluctuations during the 2020-2022 period. More specifically, the contribution in 2020 was 1.06%, decreased drastically to 0.51% in 2021 (possibly due to the pandemic), and increased slightly to 1.09% in 2022. This fluctuation indicates that parking tax revenue in Medan City remains very low and has not had a significant impact on regional finances.